Prevalence follow Bullying Students in Schools and Their Prevention: A Literature Review - Swastikaningsih, Rahmaniar Resty; Eriani, Praharesti; Hernawati, Lucia (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2023)
The bullying of teenagers is a concern of mine as it can have negative impacts on the victim such as anxiety, loneliness, low self-esteem, low levels of competition, depression, escapism, and substance abuse. The aim of this research is to identify bullying in schools and ways to prevent it. This study uses a qualitative approach with a literature review method. In this research, the data sources used are articles that can be obtained from various sources, such as reputable scientific journal databases, libraries, or the internet within the range of 2019-2022. The data set is then analyzed through inclusion and exclusion criteria stages. There were 24 articles relevant to the topic from a total of 120 analyzed articles. The results of this research found that the phenomenon of bullying has led to horrific acts of sexual harassment such as victims being forced to have sex with animals, being beaten, even forced to kiss the perpetrator's feet, crushed by a motorbike, being set on fire with cigarettes, and kicked in the genitals. Prevention methods that can be implemented include socialization to parents and the school community to increase awareness of bullying.